Fairness in international criminal trials - McDermott, Yvonne (Oxford : Oxford University Press, 2016)
With the acceptance of international criminal procedure as a self-sustaining discipline and as the tribunals established to try the most serious crimes in the former Yugoslavia, Sierra Leone, and Rwanda have completed or are beginning to wind up their activities, the time is ripe for a critical evaluation of these international criminal tribunals and their legacy. By examining the due process standards embraced by the five contemporary international criminaltribunals, the author draws conclusions about how the right to a fair trial should be interpreted in international criminal law.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2016).
Keywords: International criminal law; Fair trial; Law